2020
DOI: 10.1002/alz.12134
|View full text |Cite
|
Sign up to set email alerts
|

Incident dementia and faster rates of cognitive decline are associated with worse multisensory function summary scores

Abstract: Introduction: We created a summary score for multiple sensory (multisensory) impairment and evaluated its association with dementia. Methods: We studied 1794 adults aged 70 to 79 who were dementia-free at enrollment and followed for up to 10 years in the Health, Aging, and Body Composition Study. The multisensory function score (0 to 12 points) was based on sample quartiles of objectively measured vision, hearing, smell, and touch summed overall. Risk of incident dementia and cognitive decline (measured by two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…These results suggest that there are additive effects of multiple sensory impairments on dementia risk. Other studies found that multisensory impairment, based on objective tests of hearing, vision, smell, and touch, was strongly associated with increased risk of dementia, with worsening multisensory function associated with higher risk of dementia and faster rates of cognitive decline . Using longitudinal measures of hearing and vision collected in CHS, we extend these findings to show that longer duration of DSI is also associated with increased risk of dementia.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…These results suggest that there are additive effects of multiple sensory impairments on dementia risk. Other studies found that multisensory impairment, based on objective tests of hearing, vision, smell, and touch, was strongly associated with increased risk of dementia, with worsening multisensory function associated with higher risk of dementia and faster rates of cognitive decline . Using longitudinal measures of hearing and vision collected in CHS, we extend these findings to show that longer duration of DSI is also associated with increased risk of dementia.…”
Section: Discussionsupporting
confidence: 67%
“…Other studies found that multisensory impairment, based on objective tests of hearing, vision, smell, and touch, was strongly associated with increased risk of dementia, 44 with worsening multisensory function associated with higher risk of dementia and faster rates of cognitive decline. 45 Using longitudinal measures of hearing and vision collected in CHS, we extend these findings to show that longer duration of DSI is also associated with increased risk of dementia. We also extend previous findings that found increased risk of dementia associated with DSI based on functional hearing and visual impairments, 46 which may provide a comprehensive assessment of the association between sensory impairment and dementia by measuring sensory impairment from a functional disability approach and is a construct that affects health differently from objectively measured sensory impairment.…”
Section: Discussionmentioning
confidence: 51%
“…12,20,21,[28][29][30][31][32][33] Several small studies have shown that patients with Alzheimer disease (AD) and mild cognitive impairment have worse tactile discrimination, fine motor control, peripheral nerve CMAP amplitudes, and vibration detection than cognitive normal older adults. 5,6,34,35 In prior work, we found mixed evidence for an association with sensory peripheral nerve measures in the context of multisensory impairment, 30,36 and another study found no associations with peripheral neuropathies and cognitive decline in those with diabetes. 14 This current study clarifies and extends findings across multiple measures of sensory and motor nerve impairments by including robust adjustment for potential explanatory clinical factors and by evaluating for differences by comorbidity subgroups.…”
Section: Discussionmentioning
confidence: 76%
“…Health ABC participants identified as Black or White; therefore, our findings may not apply to other racial/ethnic groups not studied in this cohort. In addition, due to enrollment criteria, participants were generally healthier than the general population of older adults at enrollment, 36 so these findings may not be generalizable to a broader population of Black and White women and men. However, it is also possible that these associations could be stronger in a sample with a greater range in health status.…”
Section: Discussionmentioning
confidence: 93%
“…A null relationship between VI and cognitive change was also reported in 4 other longitudinal studies. 25,[50][51][52] For example, Hong et al 51 performed a prospective, population-based study of 3,654 participants of the Blue Mountains Eye Study in Australia and reported that VI was not associated with a ≥ 3 point decline in MMSE-Blind scores over 5 years (OR 0.84; 95% CI 0.40-1.79) or 10 years (OR = 1.09; 95% CI 0.52-2.30). This is in contrast to 4 longitudinal studies and one meta-analysis that have found a relationship between VI and cognitive function [12][13][14]53,54 and 1 study that found a relationship between visual acuity, used as a continuous variable, and cognitive decline.…”
Section: Discussionmentioning
confidence: 99%